2009
DOI: 10.3109/14767050903370327
|View full text |Cite
|
Sign up to set email alerts
|

A new policy for prenatal screening and diagnosis of Down syndrome for pregnant women with advanced maternal age in a public hospital

Abstract: The number of direct invasive tests was markedly reduced. With effective DS screening policy, it is possible to do away with direct invasive testing for the majority of women with AMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Four papers included data collected in the United States (US) (Marini et al, 2002;Baker et al, 2004;Kuppermann et al, 2006;Nakata et al, 2010), one from South Africa (Urban et al, 2011), two from Canada (Humphreys et al, 2003;Kaiser et al, 2004), one from China (Lo et al, 2010), one from Portugal (Nazaré et al, 2011), one from Italy (Vergani et al, 2002) and one from Israel (Muhsen et al, 2010). In seven papers, the participants were solely women (Baker et al, 2004;Kaiser et al, 2004;Kuppermann et al, 2006;Lo et al, 2010;Nakata et al, 2010;Urban et al, 2011;Vergani et al, 2002), whereas Nazaré et al (2011) andHumphreys et al (2003) included women and their partners (in the remaining two papers counselling was not mentioned). The number of participants ranged from 123 (Kaiser et al, 2004) to 163,756 (Nakata et al, 2010).…”
Section: Study Characteristicsmentioning
confidence: 97%
See 3 more Smart Citations
“…Four papers included data collected in the United States (US) (Marini et al, 2002;Baker et al, 2004;Kuppermann et al, 2006;Nakata et al, 2010), one from South Africa (Urban et al, 2011), two from Canada (Humphreys et al, 2003;Kaiser et al, 2004), one from China (Lo et al, 2010), one from Portugal (Nazaré et al, 2011), one from Italy (Vergani et al, 2002) and one from Israel (Muhsen et al, 2010). In seven papers, the participants were solely women (Baker et al, 2004;Kaiser et al, 2004;Kuppermann et al, 2006;Lo et al, 2010;Nakata et al, 2010;Urban et al, 2011;Vergani et al, 2002), whereas Nazaré et al (2011) andHumphreys et al (2003) included women and their partners (in the remaining two papers counselling was not mentioned). The number of participants ranged from 123 (Kaiser et al, 2004) to 163,756 (Nakata et al, 2010).…”
Section: Study Characteristicsmentioning
confidence: 97%
“…Six papers reported prospective studies (Vergani et al, 2002;Humphreys et al, 2003;Kaiser et al, 2004;Kuppermann et al, 2006;Muhsen et al, 2010;Nazaré et al, 2011), four reported retrospective studies (Marini et al, 2002;Baker et al, 2004;Nakata et al, 2010;Urban et al, 2011) and Lo et al (2010) utilised both prospective and retrospective approaches. Four studies were survey-based (Humphreys et al, 2003;Kuppermann et al, 2006;Muhsen et al, 2010;Nazaré et al, 2011).…”
Section: Study Characteristicsmentioning
confidence: 98%
See 2 more Smart Citations
“…3 In some clinical settings, amniocentesis or CVS for aneuploidy has been offered to all pregnant women of advanced maternal age. [4][5][6] In other circumstances or countries, discussion of invasive testing may be prompted by a high-risk screening result. 7 However, the opportunity to use non-invasive techniques for some conditions is now feasible 8 and these are increasingly available to women in some countries.…”
mentioning
confidence: 99%